In vivo brain delivery of BBB-enabled iduronate 2-sulfatase in rats - Will J. Costain; Arsalan S. Haqqani; Greg Hussack; Henk van Faassen; Etienne Lessard; Binbing Ling; Eric Brunette; Dao Ly; Hung Fang; Jennyfer Bultinck; Steven Geysens; Gwenda Pynaert; et al. (Fluids and Barriers of the CNS)
Abstract Background Iduronate-2-sulfatase (IDS) deficiency (MPS II; Hunter syndrome) is a disorder that exhibits peripheral and CNS pathology. The blood brain barrier (BBB) prevents systemic enzyme replacement therapy (ERT) from alleviating CNS pathology. We aimed to enable brain delivery of systemic ERT by using molecular BBB-Trojans targeting endothelial transcytosis receptors. Methods: Single-domain antibody (sdAb)-enzyme fusion protein constructs were prepared in Yarrowia lipolytica. sdAb affinity and BBB permeability were characterized using SPR and an in vitro rodent BBB assay, respectively. In vivo pharmacokinetic (PK) analysis was performed in rats. Quantification of fusion protein amounts were performed using LC-MS. Results Fusion proteins consisting of IDS and BBB-transmigrating sdAbs, albumin binding sdAbs or human serum albumin (HSA) were evaluated for their in vitro BBB permeability. IGF1R3H5-IDS was selected for in vivo PK analysis in rats. IDS and IGF1R3H5-IDS exhibited very short (< 10 min) serum half-life (t1/2α), while constructs containing either HSA or anti-serum albumin sdAbs (R28 or M79) showed 8–11 fold increases in the area under the curve (AUC) in serum. CSF analysis indicated that IGF1R3H5 increased brain exposure by 9 fold (AUC) and constructs containing HSA or R28 exhibited 42–52 fold increases. Quantitation of brain levels confirmed the increased and sustained delivery of IDS to the brain of HSA- and R28-containing constructs. Lastly, analysis of brain fractions demonstrated that the increases in brain tissue were due to parenchymal delivery without fusion protein accumulation in brain vessels. Conclusions These results demonstrate the utility of IGF1R-targeting sdAbs to effect brain delivery of lysosomal enzymes, as well as the utility of serum albumin-targeting sdAbs in t1/2 extension, to increase brain delivery of rapidly cleared enzymes.